2017
DOI: 10.1002/ccd.27158
|View full text |Cite
|
Sign up to set email alerts
|

Acute changes in histopathology and intravascular imaging after catheter‐based renal denervation in a porcine model

Abstract: Objectives: We first aimed to identify the histopathological changes occurring immediately after renal denervation (RDN) with radiofrequency energy, and then to assess the feasibility of determining procedural success using currently available clinical intravascular imaging techniques.Background: Catheter-based RDN has been used as an alternative therapy for hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Our findings demonstrate that RDN caused injury to the vascular intima and media; and the in vitro endothelium-independent tension assay showed that renal arterial relaxation function decreased after the RDN. This result is due to elastic fiber breakage, vascular smooth muscle cell degeneration and necrosis, which was also consistent with the thin media and reduced myofilament density in ablated medial smooth muscle cells after RDN in Sakaoka’s study [28]. Unfortunately, we did not detect endothelium-dependent vascular relaxation function and only detected AKT/eNOS pathway-related protein expression, which explained the endothelial dysfunction molecularly.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings demonstrate that RDN caused injury to the vascular intima and media; and the in vitro endothelium-independent tension assay showed that renal arterial relaxation function decreased after the RDN. This result is due to elastic fiber breakage, vascular smooth muscle cell degeneration and necrosis, which was also consistent with the thin media and reduced myofilament density in ablated medial smooth muscle cells after RDN in Sakaoka’s study [28]. Unfortunately, we did not detect endothelium-dependent vascular relaxation function and only detected AKT/eNOS pathway-related protein expression, which explained the endothelial dysfunction molecularly.…”
Section: Discussionsupporting
confidence: 85%
“…First, the findings obtained from the normotensive swine may not be applicable to patients with hypertension. However, the normotensive swine is the standard animal model for assessing RDN device safety, because of its anatomical and physiological similarity to humans . Second, because of the small number of animals, adverse findings with a low incidence may have been missed.…”
Section: Discussionmentioning
confidence: 99%
“…The safety of RF‐RDN on the main RA has been confirmed in >1,000 patients, and histopathological changes induced by RF‐RDN around the main RA were assessed in several animal studies, However, the safety of RF‐RDN on the branch RA remains unclear. As the diameter of the branch RA is smaller than that of the main RA, there is a potential risk of disruption or stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…A catheter provided radial access to minimize vascular complications as well as femoral access. The safety and efficacy of the system were validated by the preclinical animal studies [11][12][13]. This system obtained CE approval in March 2013.…”
Section: Methodsmentioning
confidence: 99%